FEASIBILITY OF HADANAH FOR ACTIVE SMOKER MOTHERS: MAQASHID SYARIAH ANALYSIS OF ARTICLE 156(C) OF THE COMPILATION OF ISLAMIC LAW - Akmal Fathi Rayyan Fadli; Muhamad Arifin (Journal Analytica Islamica, 2026)
The transfer of child custody in Islamic family law may be granted when the holder of hadanah is unable to ensure the child’s safety, as stipulated in Article 156(c) of the Compilation of Islamic Law (KHI). There is a gap in legal scholarship regarding the suitability of an active smoker as a custodial parent. This normative legal study aims to analyze Article 156(c) of the KHI through the perspective of maqashid syariah regarding cases involving mothers who are active smokers. The results of the study indicate that Article 156(c) of the KHI establishes hadanah as a conditional right. In judicial practice, judges have begun to apply a risk-based approach regarding the dangers of exposure to cigarette smoke. The novelty of this study emphasizes that active smoking by a caregiver is not a neutral condition, but rather a form of dharar that threatens hifz al-nafs (protection of life) and hifz al-nasl (protection of offspring) of the child. Thus, treating active smoking as a risk factor in custody and a basis for transferring custody is normatively valid and consistent with the maqashid of Sharia in protecting the best interests of the child.